Cutaneous myxidiosis in European eel, Anguilla anguilla (Linnaeus, 1758): histopathology, histochemistry and laminin immunohistochemistry. Issue 7 (3rd November 2015) - Manera, M; Borreca, C; Dezfuli, B S
Abstract: Histopathology, histochemistry and immunohistochemistry of the integument of European eel, Anguilla anguilla (Linnaeus, 1758), infected by Myxidium sp. are reported. Skin samples from affected and unaffected eels were dissected, formalin fixed, paraffin embedded, sectioned and stained with H&E, Periodic acid–Schiff's staining method, Alcian Blue 8 GX pH 2.5/Periodic acid–Schiff's and McCallum‐Goodpasture's Gram stain. Moreover, immunohistochemistry was performed using a primary polyclonal laminin antibody. Histologically, cysts (diameter 2–3 mm) were observed mainly under the scale pockets, encircled by a thin collagen layer, lined by elongated, flattened fibroblasts and containing bipolar, PAS‐ and Gram‐positive spores with opposite polar capsules. The epidermis stretched by the underlying cyst appeared dysplastic, thinned with a significant reduction in mucous cells number. Only inconsistent and aspecific inflammatory reaction was noted around the cysts at the dermis/epidermis interface. Intense laminin‐like protein immunolabel was documented in the plasmodial ectoplasm and related to host anergia. This was the first report of laminin immunolabel in a member of the Myxozoa. Epidermal dysplasia represents likely an aspecific response against the underlying tensile force exerted by the developing parasite cyst, while fibroblast and collagen encapsulation denote a parasite‐driven host response protecting, rather than harming, the encircled parasite.